Inhibition of Sporulation of Chicken Eimeria by Tannin from Kameng Leaf Extract - Thanasut, Khompakorn; Jarujareet, Wipaporn; Rungthong, Korrachark; Phruksarudi, Chinnakrit (Journal of Mahanakorn Veterinary Medicine, 2024)
Kameng is a plant native to Central and South America. The species has spread to temperate and tropical countries. In Thailand, it can be found everywhere in every region. The main active ingredient against protozoa is tannin. Since Thailand is located in a tropical area suitable for the growth of Eimeria spp., this protozoa in chickens is a disease that causes dysentery, diarrhea and a higher morbidity and mortality rate and the growth rate was decreased. This results in economic damage to farmers. The aim of this study was to investigate the efficacy of a Kameng leaf extract on the sporulation rate of eimeria oocysts in broiler (in vitro). Experiment was separated into 6 groups. The tannin concentrations from Kameng leaf extract were at 70, 700, 7,000 and 70,000 ppm, the Toltrazuril anticoccidial group and the control group. The morphological characteristics of oocysts and sporulation rate of each experimental group were compared after mixing the leaf extract with oocysts at 24, 48 and 72 hours. The inhibition of the sporulation depends on the concentration of tannin. Tannin from Kameng leaf extract at a concentration of 70,000 ppm resulted in oocyst wall deformity and oocyst wall rupture the most. In addition, the sporulation rate was the lowest compared to each experimental group. According to the results of the study, the altered oocyst wall and reduced sporulation rate reduce the pathogenic capacity in chickens.